Development of a feature-recognition and measurement path generation system based on NURBS surfaces for 5-axis on-machine measurement - Yeo, Inwoong; Song, Inho; Cheon, Sang Uk; Yang, Jeongsam (Journal of Mechanical Science and Technology, 2019)
On-machine measurement (OMM), which is used to measure the machined surfaces of a workpiece during or after the machining of the workpiece, enables direct measurement within the workspace without moving the workpiece. However, although the three-dimensional geometric shape created by computer-aided design systems include various features, because such features are converted into non-uniform rational B-spline (NURBS) surfaces during OMM, measurement deviation occurs between a feature and its corresponding NURBS surface. In this paper, we suggest a method to generate the measurement path for 5-axis OMM in a way that recognizes the features necessary for measurement from NURBS surfaces whose feature data set was removed during the conversion processes. To verify the reliability of the measurement path generation system named OMV+, which was developed using the above method, we carried out an experiment to compare the measurement path that defines the measuring point on the feature and the path that defines the measuring point on the NURBS surface with the measured result using the touch probe on the machined workpiece.
Keywords: Computer aided design systems; Conversion process; Feature recognition; Measurement deviations; Measuring points; Non-uniform rational B-splines; NURBS surface; On-machine measurement; Feature recognition; Measurement path; Measuring point; NURBS surface; On-machine measurement (OMM)